Public transport provision under agglomeration economies - Hörcher, Daniel; De Borger, Bruno; Seifu, Woubit; Graham, Daniel J. (Regional science and urban economics, 2020)
The purpose of this paper is to investigate, using both theoretical and numerical analysis, the impact of agglomeration externalities on short-run policy decisions in public transport, i.e. socially optimal pricing, frequency setting, and subsidisation. We develop a simple two-mode model in which commuters can opt for car or public transport use; car use leads to congestion, and public transport is subject to crowding. Allowing for agglomeration externalities, we show the following results. First, if car use is correctly priced for congestion, agglomeration benefits imply substantially lower public transport fares and higher frequencies. They neutralise to some extent the pressure to increase fares to correct the crowding externality. Second, as a consequence, agglomeration benefits justify low cost recovery ratios in public transport. Assuming an agglomeration elasticity of 1.04, a value well within the range of reported elasticities, numerical implementation of the model finds that cost-recovery ratios are 35.8% lower than in the absence of the productivity externality. Third, interestingly, the effect of agglomeration benefits on fares and frequency is much smaller if road use is exogenously under-priced. In this case, any modal shift induced by lower public transport fares has opposing agglomeration effects on the two modes, since agglomeration benefits are not mode-specific. •We consider agglomeration economies in the optimisation of public transport supply.•The agglomeration externality can be similar in magnitude to marginal crowding costs.•Agglomeration economies tend to increase the welfare maximising subsidy.•Substitution with under-priced road use limits ability to internalise agglomeration.